Genomic and phenotypic characterization of antimicrobial resistance in clinical Nocardia species isolates - Song, Ziyu; Du, Bingqian; Yuan, Min; Shen, Jirao; Xu, Shuai; Guan, Wanchun; Lu, Binghuai; Li, Zhenjun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAntimicrobial resistance is prevalent across Nocardia species, with varying resistance profiles among different species, which poses significant challenges to effective treatment strategies. Our study aimed to assess the antimicrobial susceptibility profiles of various Nocardia species and investigate the potential correlation between resistance phenotypes and their underlying genotypes.MethodsThis study analyzed 148 clinical Nocardia isolates from 13 provinces in China. Minimum inhibitory concentrations (MICs) for 15 antimicrobial agents were determined using the microbroth dilution method. Whole genome sequencing (WGS) was performed for all isolates, followed by bioinformatics analyses integrated with 70 human-sourced Nocardia genomes in the National Center for Biotechnology Information (NCBI), encompassing species verification, phylogenetic analysis, and the identification of antimicrobial resistance genes (ARGs).ResultsAverage Nucleotide Identity (ANI) analysis reclassified several misidentified isolates and revealed 14 potentially novel Nocardia species, underscoring the taxonomic complexity within this genus. Nocardia species exhibited distinct resistance profiles: Nocardia farcinica demonstrated elevated resistance to cephalosporins and tobramycin; Nocardia otitidiscaviarum showed broad resistance to β-lactams and quinolones; and Nocardia cyriacigeorgica exhibited resistance to quinolones, cefepime, and cefoxitin. Notably, clarithromycin resistance was consistently high across all species. Moreover, 38.51% of Nocardia isolates are resistant to two or more commonly used antibiotics, which revealed widespread multidrug resistance (MDR). Strong genotype–phenotype correlations were observed, including sul1 in sulfamethoxazole/trimethoprim-resistant N. farcinica, blaAST-1 in β-lactam-resistant N. otitidiscaviarum, and tetA/B(58) across tetracycline-intermediate isolates. Additionally, resistance mechanisms beyond ARGs were observed, including species-specific presence of warA and aph(2’’), and gyrA mutations largely correlating with ciprofloxacin resistance. Nonetheless, resistance in some strains lacking known resistance determinants indicates the presence of uncharacterized mechanisms.ConclusionsThese findings provide critical insights into the drug resistance patterns of Nocardia strains and antimicrobial resistance genes, highlighting the importance of ongoing genomic surveillance and personalized treatments.